Transcultural communication through global Englishes : an advanced textbook for students - Baker, Will (Language teacher); Ishikawa, Tomokazu (Abingdon, Oxon : Routledge, 2021)
"This textbook introduces current thinking on English as a global language and explores its role in intercultural and transcultural communication. It covers how English functions as a lingua franca in multilingual scenarios alongside other languages in a wide variety of global settings, and the fluid and dynamic links between English, other languages, and cultural identities and references. The implications for English language teaching, academia, business, and digital communication are explored. Contemporary research and theory are presented in an accessible manner, illustrated with examples from current research, and supported with discussions and tasks to enable students to relate these ideas to their own experiences, needs, and interests. Each chapter contains activities to help students orientate towards the topic, reflect on personal experiences and opinions, and check their understanding; a detailed glossary of key terminology in Global Englishes and Intercultural Communication is provided as well. Exploring in-depth the links between Global Englishes, Intercultural and Transcultural Communication research, this is key reading for all advanced students and researchers in Global or World Englishes, English as a Lingua franca, and Intercultural Communication"--
Includes bibliographical references and index.
Keywords: English language -- Foreign countries; Intercultural communication; English language -- Study and teaching -- Foreign countries